Requests for euthanasia in general practice before and after implementation of the Dutch Euthanasia Act - van Alphen, Jojanneke E (Royal College of General Practitioners, 2010)
BACKGROUND: The Netherlands was the first country in the world to implement a Euthanasia Act in 2002. It is unknown whether legalising euthanasia under strict conditions influences the number and nature of euthanasia requests. AIM: To investigate changes in the number of, and reasons for, requests for euthanasia in Dutch general practice after implementation of the Euthanasia Act. DESIGN OF STUDY: Retrospective dynamic cohort study comparing 5 years before (1998–2002) and 5 years after (2003–2007) implementation of the Act. METHOD: Standardised registration forms were used to collect data on requests for euthanasia via the Dutch Sentinel Practice Network. This network of 45 general practices is nationally representative by age, sex, geographic distribution, and population density. RESULTS: The mean annual incidence of requests before implementation amounted to 3.1/10 000 and thereafter to 2.8/10 000 patients. However, trends differed by sex. The number of requests by males decreased significantly from 3.7/10 000 to 2.6/10 000 (P = 0.008); the requests by females increased non-significantly from 2.6/10 000 to 3.1/10 000. Before and after implementation, cancer remained the major underlying disease for requesting euthanasia: 82% versus 77% for men; 73% versus 75% for females. Pain was a major reason for a request, increasing in the period before implementation (mean 27%), but declining in the period thereafter (mean 22%). Loss of dignity became a less important reason after implementation (from 18% to 10%, P = 0.04), predominantly due to a marked decrease in the number of females citing it as a reason (from 17% to 6%, P = 0.02). CONCLUSION: There was no increase in demand for euthanasia after implementation of the Euthanasia Act. Pain as a reason for requesting euthanasia showed an increasing trend before implementation, but declined thereafter. Loss of dignity as a reason declined, especially in females.